2014
DOI: 10.3109/10903127.2014.967427
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene in Emergency Medical Services

Abstract: This study demonstrates that EMS providers are potential vectors of microorganisms if proper hand hygiene is not performed properly. Since EMS providers treat a variety of patients and operate in a variety of environments, providers may be exposed to potentially pathogenic organisms, serving as vectors for the exposure of their patients to these same organisms. Proper application of accepted standards for hand hygiene can help reduce the presence of microbes on provider hands and subsequent transmission to pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 14 publications
2
30
0
2
Order By: Relevance
“…To elucidate the level of microbial contamination on PRS, we sampled the torso and sleeve from the uniforms [11] and the upper side, and the palm of the dominating hand from the provider last in charge of a patient course [13]. …”
Section: Methodsmentioning
confidence: 99%
“…To elucidate the level of microbial contamination on PRS, we sampled the torso and sleeve from the uniforms [11] and the upper side, and the palm of the dominating hand from the provider last in charge of a patient course [13]. …”
Section: Methodsmentioning
confidence: 99%
“…In hospital settings, HAIs are major causes of longer stays, long‐term disability, higher treatments costs, and increased antimicrobial drug resistance and have consistently been linked to increased morbidity and mortality (Erasmus et al, ; Lapão, Marques, & Gregório, ). Numerous studies provide evidence that contamination on health‐care workers' (HCWs) hands are the most important source of transmission of pathogens in hospitals, and such contamination occurs from touching patients or the objects in the environment surrounding them (Farhoudi et al, ; Teter, Millin, & Bissell, ).…”
Section: Introductionmentioning
confidence: 99%
“…This study has highlighted that there are cultural issues acting as disincentives to appropriate IPC practices in paramedicine that require further investigation. Poor compliance where guidance policies exist has been demonstrated to be an issue both in Australia and internationally (14,15,(37)(38)(39)(40)(41)(42)(43)(44)(45). Evidence from hospital post-acute care areas suggests that accepted cultural norms that lower compliance with recommended healthcare practices (46) can be improved over time through collaborative interventions between staff and management (15,47).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from hospital post-acute care areas suggests that accepted cultural norms that lower compliance with recommended healthcare practices (46) can be improved over time through collaborative interventions between staff and management (15,47). Previous studies have suggested that it may be effective to use staff to champion causes and promote transformational change (14,46). Two of the experts in our study noted that compliance with recommended IPC practices improved during a pandemic, which suggests that an increased perception of the threat of a serious infectious agent could be an important factor that influences behaviour change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation